2018
DOI: 10.1002/pssa.201700554
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of GaN‐Based Direct Current and Alternating Current High Voltage Light‐Emitting Diodes

Abstract: In this work, one type of direct current high voltage light‐emitting diode (DC‐HV LED) and six types of alternating current high voltage LEDs (AC‐HV LEDs) are demonstrated. Comparative current‐voltage (I–V) and light output power (LOP)‐current (L‐I) characteristics are performed between 24 V DC‐HV LED and 24 V AC‐HV LEDs with eight working cells. The AC‐HV LED has relatively larger wall‐plug efficiency (WPE) than DC‐HV LED over a current density range from 0 to 152 A cm−2. The effect of the layouts on the opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Dividing a large area LED chip into numerous serially connected LED cells improved the brightness of GaN-based LEDs and at the same time avoided the poor current spreading problem [21]. HV-LEDs can provide large optical power in small size (over 350 mW in a size of 896 μm × 432 μm, as reported in [22]). Single-chip highvoltage LEDs also enable simplified driver design, because its operation voltage is closer to mains or DC voltage supplies [23].…”
Section: Introductionmentioning
confidence: 89%
“…Dividing a large area LED chip into numerous serially connected LED cells improved the brightness of GaN-based LEDs and at the same time avoided the poor current spreading problem [21]. HV-LEDs can provide large optical power in small size (over 350 mW in a size of 896 μm × 432 μm, as reported in [22]). Single-chip highvoltage LEDs also enable simplified driver design, because its operation voltage is closer to mains or DC voltage supplies [23].…”
Section: Introductionmentioning
confidence: 89%
“…That is because the strong electric field will lead to a harmful halide migration and the present chlorine-rich and bromine-rich areas in the perovskite film, resulting in phase separation and a red shift of the EL spectrum . Therefore, it is a promising method for the achievement of blue PeLEDs with a stable spectrum through electrical regulation. , Tan et al first demonstrated pure blue PeLEDs with a stable spectrum, driven by a square wave AC voltage . As shown in Figure d, the authors built the PeLEDs with the structure of ITO/PEDOT:PSS/perovskite/TPBi/LiF/Al.…”
Section: Ac-driven Perovskite El Devicesmentioning
confidence: 99%
“…119 Therefore, it is a promising method for the achievement of blue PeLEDs with a stable spectrum through electrical regulation. 120,121 Tan et al first demonstrated pure blue PeLEDs with a stable spectrum, driven by a square wave AC voltage. 122 As shown in Figure 13d, the authors built the PeLEDs with the structure of ITO/ PEDOT:PSS/perovskite/TPBi/LiF/Al.…”
Section: ■ Ac-driven Perovskite El Devicesmentioning
confidence: 99%
“…Some of the latest research has demonstrated that gallium nitride (GaN)-based LEDs can be operated without an AC-DC converter being required, revealing their potential for application in energyefficient and reliable LED lighting systems. [51][52][53][54][55][56] Although ACdriven TMDC monolayer LEDs have been demonstrated recently, it is worth noting that several important issues, such as device upscaling difficulty and a small emission area, still remain unresolved at the current stage.…”
Section: Introductionmentioning
confidence: 99%